Toward implementing a fully automated truck guidance system at a seaport: Identifying the roles, costs and benefits of logistics stakeholders - Valentin Carlan; Dries Naudts; Pieter Audenaert; Bart Lannoo; Thierry Vanelslander (Journal of Shipping and Trade (JST), 2019)
The seaport-hinterland access infrastructures become more saturated leading to extra unpredictable costs for logistics operators. To keep their services competitive, infrastructure managers (such as port authorities) seek new approaches in managing and delivering information to their users. Starting from existing technological advancements and exploring the declared opportunities enabled by (near) future ones, a range of solutions (e.g. real-time information platforms, dynamic information boards or digital on-request notification solutions) can be pursued. This research investigates how an advanced truck guidance system (TGS) leverages on technology and leads to more efficient resource (infrastructure, equipment and labour) usage. The current paper merges two perspectives. The first conducts interviews with representatives of different logistics stakeholders to highlight their data needs. The second perspective is given by a review of information communication technology (ICT) innovative trends. These two perspectives provide an up-to-date overview of both needs (demand) and opportunities (supply) that challenge logistics stakeholders. This study proposes a TGS architecture that merges the two perspectives and identifies a stepwise approach to implement it. Therefore, the roles, costs and benefits brought to the logistics stakeholders are highlighted for each step. The key findings of this study show that road transport operators would benefit from operational savings and increased performance, while the other supply chain stakeholders can benefit from setting up a more reliable planning, better managing their infrastructure and developing added-value services for clients. To enable these benefits, the port administration could take the facilitator role and cover the TGS's development costs.
Keywords: 650; Truck guidance system; Seaport; Users benefits; Implementation strategies